La gota madre: Revelación del río hablador - Camargo Reyes, Camila Andrea (Pontificia Universidad Católica del Perú, 2025)
Exploring Lima’s most polluted river, the Rímac, from its role in pre-Hispanic worldview to its current condition in the city, means immersing into its physical, symbolic and cultural deterioration. Along this journey, there emerges, like a revelation silenced by the metropolis: The Mother Drop, a proposal transformed into an installation project that seeks to restore the river as a being, reinforcing the bond between humans and “Earth Beings” (De la Cadena, 2015), a concept that recognizes the agency of natural entities. Through a ceramic filtration system, it proposes a methodological collaboration with the riverbed and natural elements to create a sustainable alternative for the river’s symbolic recovery; while at the same time inviting reflection on the act of purifying its waters towards the future.

Explorar el río más contaminado de Lima, el Rímac, desde su rol en la cosmovisión prehispánica hasta su condición actual en la ciudad, implica sumergirse en su deterioro físico, simbólico y cultural. En este recorrido, emerge, como una revelación silenciada por la urbe: La Gota Madre, propuesta transformada en un proyecto instalativo que busca restituir al río como ser reforzando el vínculo entre el humano y los “seres tierra” (De la Cadena, 2015), concepto que reconoce la agencia de los seres naturales. A través de un sistema de filtración cerámica, se propone una colaboración metodológica con el cauce y los elementos naturales para crear una alternativa sostenible de recuperación simbólica del río; al mismo tiempo que invita a reflexionar sobre la acción de la purificación de sus aguas hacia el futuro.
The Mother Drop: Revelation of the talking river
Keywords: Rimac river; Earth Beings; Ceramic ﬁltration; Water recovery; Decolonial; Río Rímac; Seres tierra; Filtración cerámica; Recuperación del agua; Decolonial; https://purl.org/pe-repo/ocde/ford#6.04.01